2012
DOI: 10.1016/j.cognition.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A claw is like my hand: Comparison supports goal analysis in infants

Abstract: Understanding the intentional relations in others' actions is critical to human social life. Origins of this knowledge exist in the first year and are a function of both acting as an intentional agent and observing movement cues in actions. We explore a new mechanism we believe plays an important role in infants' understanding of new actions: comparison. We examine how the opportunity to compare a familiar action with a novel, tool use action helps 7- and 10-month-old infants extract and imitate the goal of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 36 publications
8
71
0
Order By: Relevance
“…R. Soc. B 369: 20130181 instances, under the right conditions [41]. As we have highlighted in this paper, the cognitive processes involved in both action production and action understanding describe actions in terms their relation to a goal.…”
Section: Infants' Actions Support the Interpretation Of Novel Actionsmentioning
confidence: 94%
See 2 more Smart Citations
“…R. Soc. B 369: 20130181 instances, under the right conditions [41]. As we have highlighted in this paper, the cognitive processes involved in both action production and action understanding describe actions in terms their relation to a goal.…”
Section: Infants' Actions Support the Interpretation Of Novel Actionsmentioning
confidence: 94%
“…We evaluated this hypothesis by attempting to teach seven-month-old infants about a novel action, the use of a claw-shaped tool to grasp objects [41]. As noted earlier, prior findings had shown that infants at this age do not spontaneously view actions with a claw as goal directed.…”
Section: Infants' Actions Support the Interpretation Of Novel Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this analysis, 9-month-olds failed at a preference task in which an agent placed the back of her hand against object-A in the familiarization trials, instead of grasping it; because infants could not infer the goal of this baffling back-of-hand action, they looked equally at the new-and old-object events (Woodward, 1999). Several investigations have taken advantage of this negative result to examine what experiences might lead infants to view the back-of-hand action as goal-directed (e.g., Bíró et al 2014;Király et al 2003; for similar investigations with other novel actions, e.g., Gerson & Woodward 2012. In one experiment, for example, an experimenter and 12-month-olds first took turns lifting Velcrocovered blocks using a Velcro band worn on the back of their hands (Bíró et al 2014).…”
Section: Goalsmentioning
confidence: 99%
“…Similarly, it has been suggested that infants code actions at this same level of analysis, because goals can be represented more abstractly than movements, and thus infants can generalize their representations more readily to others' goal-directed actions even if the specific movements vary . For instance, infants learn to generalize one instance of a goal-based action (e.g., goal-directed reaching) to a novel situation in which they observe someone reaching with a mechanical claw, as long as their grasping actions co-occur with the claws' grasping and releasing toys (Gerson & Woodward, 2012).…”
Section: Representation Of Movements Versus Goalsmentioning
confidence: 99%